“MEDICAL AND SOCIAL PROBLEMS OF STUDENTS' LIFESTYLE AND HEALTH DURING THE COVID 19 PANDEMIC” - Muyassarova Mukhabbat Mukhammadievna (The Conference Hub, 2025)
Protecting students' health is one of the most important social responsibilities of society. Students of higher education institutions are the socio-economic, intellectual and creative potential of the country. At the same time, the student community can be classified as a high-risk group, since the complex age-related problems of students are aggravated by the negative impact of the crisis on almost all key sectors of society and the state.